Battle of the strategies: diet versus drug therapy for gout - O. V. Zhelyabina; M. S. Eliseev; A. M. Lila (Современная ревматология)
The best results in combating gout are achieved through a combination of diet and drug therapy. Urate-lowering therapy, which includes febuxostat, has been shown to be more effective and convenient than diet when it comes to achieving and maintaining target uric acid (UA) levels in gout patients. Febuxostat, a xanthine oxidase inhibitor, helps to reduce UA levels in the blood by blocking its formation. This helps prevent the deposition of urate crystals in joints and tissues and reduces the frequency and severity of gout attacks. At the same time, a diet of low purine foods may also have some effect on UA levels. Diet can improve the results of drug treatment by reducing the need for medications and minimizing the risk of side effects. However, without adequate drug therapy, diet will not produce the desired results. Therefore, febuxostat remains the preferred urate-lowering treatment option for gout, especially given its proven efficacy in these patients.